The effect of climate change on the western rock lobster (Panulirus cygnus) fishery of Western Australia - Caputi, N.; Melville-Smith, Roy; de Lestang, S.; Pearce, Alan; Feng, M. (Canadian Science Publishing (formerly NRC Research Press), 2010)
Environmental factors such as the Leeuwin Current (influenced by the El Niño – Southern Oscillation cycle) and westerly winds in late winter – spring significantly affect puerulus settlement of the western rock lobster (Panulirus cygnus) fishery. Climate change is causing an increase in water temperature that is seasonally variable, a weakening of westerly winds in winter, and an increase in the frequency of El Niño events. Rising water temperatures over 35 years may have resulted in a decrease in size at maturity and size of migrating lobsters from shallow to deep water, increases in abundance of undersized and legal-sized lobsters in deep water relative to shallow water, and shifts in catch to deep water. The size of migrating lobsters is related to the water temperature about the time of puerulus settlement (four years previously). Climate change effects on puerulus settlement, catchability, females moulting from setose to non-setose, timing of moults, and peak catch rates are assessed. As climate change models project that the warming trend will continue, these biological trends are likely to continue. The changes may have negative (increasing frequency of El Niño events) or positive (increasing water temperature) implications for the fishery, which need to be taken into account in stock assessments and management.